Kontribusi Dakwah Ulama dalam Membentuk Wacana Politik Kontemporer di Indonesia (Jurnal Komunikasi Islam, 2025)
Da’wah plays a strategic role in shaping public opinion, guiding the political preferences of the faithful, and framing national issues from an Islamic perspective. This study examines the contribution of Islamic preachers to contemporary political discourse in Indonesia. It employs a qualitative methodology, utilizing a literature review and discourse analysis to explore how da’wah narratives are produced, disseminated, and received in the context of modern politics. The findings indicate that the preaching of religious scholars contributes to both socio-political polarization and integration, serving as a tool for fostering political awareness, legitimizing power, and facilitating social mobilization. The development of digital media expands the reach of such preaching, thereby strengthening the role of religious scholars in shaping public political discourse in Indonesia. Overall, the preaching of religious scholars plays a significant role in shaping the contours of contemporary political discourse in Indonesia.